Letter to Governor Pat Brown from Jane Tolmach and Adele Leopold - Jane Tolmach::::::; Adele Leopold:::::: (1971)
In this January 1, 1971 letter, Jane Tolmach and Adele Leopold invite Secretary of State Edmund G. "Jerry" Brown Jr. to attend the Key Women Award Party on January 16, 1971, at the Beverly Hilton in Los Angeles. The event honors women volunteers who supported Democratic nominees in the 1970 general election, and Brown is especially encouraged to attend given the significance of his recent victory. The letter emphasizes that these volunteers would appreciate hearing from one of their successful candidates.